Pharmacological Inhibition of p38 Mitogen-Activated Protein Kinases Affects KC/CXCL1-Induced Intraluminal Crawling, Transendothelial Migration, and Chemotaxis of Neutrophils In Vivo - Najia Xu; Mokarram Hossain; Lixin Liu (Mediators of Inflammation)
p38 mitogen-activated protein kinase (MAPK) signalling is critical in the pathophysiology of a variety of inflammatory processes. Leukocyte recruitment to the site of inflammation is a multistep process governed by specific signalling cascades. After adhesion in the lumen, many leukocytes crawl to optimal sites at endothelial junctions and transmigrate to extravascular tissue in a Mac-1-dependent manner. The signalling mechanisms that regulate postadhesion steps of intraluminal crawling, transmigration, and chemotaxis in tissue remain incompletely understood. The present study explored the effect of p38 MAPK inhibitor SB203580 on various parameters of neutrophil recruitment triggered by chemokine KC (CXCL1) gradient. Neutrophil-endothelial interactions in microvasculature of murine cremaster muscle were determined using intravital microscopy and time-lapsed video analysis. SB203580 (100 nM) did not change leukocyte rolling but significantly attenuated neutrophil adhesion, emigration, and transmigration and impaired the initiation of neutrophil crawling and transmigration. In response to KC chemotactic gradient, SB203580 significantly reduced the velocity of migration and chemotaxis index of neutrophils in tissue. The upregulation of Mac-1 expression in neutrophils stimulated by KC was significantly blunted by SB203580 in vitro. Collectively, our findings demonstrate that pharmacological suppression of p38 MAPK significantly impairs multiple steps of neutrophil recruitment in vivo.